2020
DOI: 10.1111/jfb.14483
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy identifies a new stingray species of the genus Hypanus Rafinesque, 1818 (Dasyatidae, Myliobatiformes), from the Tropical Southwestern Atlantic

Abstract: An integrative approach by the congruence of genetics, morphology and ecological niche modelling (ENM) was used to delimit a new species of Hypanus (Rafinesque, 1818), a recently resurrected genus of marine stingrays comprising eight species, five of which occur in the western Atlantic. The species with the widest distribution, Hypanus americanus (Hildebrand and Schroeder, 1928), from the northeastern coast of the United States to southeastern Brazil, was demonstrated to be paraphyletic based on protein-coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 96 publications
(153 reference statements)
1
27
0
Order By: Relevance
“…(Marceniuk et al, 2019). Similarly, molecular data identified Narcine brasiliensis and Mustelus canis (Guimarães-Costa et al, 2020;Rodrigues-Filho et al, 2020) while integrative analyses based on morphological, genetic and ecological studies recorded H. berthalutzae (Pentean et al, 2020) for this region. These data highlight the importance of focusing on the diversity of elasmobranchs in the north coast of Brazil, as recent studies have identified distinct results on the species composition in this group of fishes.…”
Section: Diversity Of Elasmobranchs In the Amazon Coastmentioning
confidence: 83%
See 1 more Smart Citation
“…(Marceniuk et al, 2019). Similarly, molecular data identified Narcine brasiliensis and Mustelus canis (Guimarães-Costa et al, 2020;Rodrigues-Filho et al, 2020) while integrative analyses based on morphological, genetic and ecological studies recorded H. berthalutzae (Pentean et al, 2020) for this region. These data highlight the importance of focusing on the diversity of elasmobranchs in the north coast of Brazil, as recent studies have identified distinct results on the species composition in this group of fishes.…”
Section: Diversity Of Elasmobranchs In the Amazon Coastmentioning
confidence: 83%
“…A potential obstacle to a proper identification of the species was the lack of whole specimens to be used as a voucher for morphological identification as well as the absence of sequences in public datasets for comparative analyses (Rodrigues-Filho et al, 2020). In recent years, studies based on molecular identification of stingray species have allowed both the identification of valid species and the registration of new occurrences and new species (Guimarães-Costa et al, 2020;Pentean et al, 2020). In a recent study, Rodrigues-Filho et al ( 2020) identified nine ray species on the Amazon coast using DNA barcodes.…”
Section: Diversity Of Elasmobranchs In the Amazon Coastmentioning
confidence: 99%
“…Because bonnethead sharks are stenohaline species, it has been documented that salinity plays a role in their distribution and movement (Ubeda et al ., 2009), so unsuitable habitats might act as geographical barriers restricting species distribution (Alvarado‐Serrano & Knowles, 2014), as has been documented for other megafauna including stingrays ( Hypanus spp.) (Petean et al ., 2020), dolphins ( Sotalia spp., Stenella frontalis ) (Caballero et al ., 2013, 2018) and the sawfish ( Pristis pristis ) (Faria et al ., 2013). As a consequence of the lack of gene flow with adjacent populations the Brazilian S .…”
Section: Discussionmentioning
confidence: 99%
“…Sharks are mobile species that are widely distributed across large geographic areas and yet, recent studies provide evidence of strong population structure on finer spatial scales than expected based on movement potential (Ashe et al ., 2015; Chapman et al ., 2015; Petean et al ., 2020; Portnoy et al ., 2015). Some widely distributed elasmobranchs have proven to be a species complex with each of the cryptic species having a much narrower distribution, which can expose them to different management jurisdictions and potential threats (Fields et al ., 2016; Lim et al ., 2010; Naylor et al ., 2012; Portnoy et al ., 2010; Quattro et al ., 2006, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(Zhang et al, 2020;Crossley et al, 2002). Climatic variations can aid evolutionary divergence (Petean et al, 2020;Rissler and Apodaca, 2007) by fostering species adaptation to new climatic environs (Iannella et al, 2019). In addition, the cosmopolitan distribution of O. ulvifolia in Africa is supported by our simulations, which show that the species can persist in a broad range of environmental conditions.…”
Section: Discussionmentioning
confidence: 99%